Animosity. Volume 3, The swarm - Bennett, Marguerite; Bennett, Marguerite (Aftershock Comics, LLC, 2018)
"Jesse and her animal companions continue their road trip to California, picking up ex-Animilitary member Kyle along the way. But nothing can ever be easy, and soon Jesse and the others are caught between a hive of bees and the perfect-seeming Old Gold Commune. Tensions run high as betrayal stings Jesse in a way she could have never imagined. Can Kyle shed his humanity long enough to aid Jesse in her quest? Can Sandor forsake his bestial nature in order to save that which he loves?"--Page 4 of cover